Efforts To Promote Infrastructure Through The Making Of A Light Steel Frame Bridge With Composite Floor In Nanggela Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The Civil Engineering Department of Road and Bridge Design Engineering Study Program in order to support the government's efforts to advance disadvantaged villages in infrastructure, contribute to advancing infrastructure in the village of Nanggela. Contributions are given in the form of community service activities, namely: construction of a lightweight steel bridge with composite floors that connects the villages of Nanggela – Nanggerang funded by the Politeknik Negeri Jakarta's research and community service unit. The implementation method carried out includes the preliminary stage, Bridge structure design stage, proposal preparation stage to UP2M PNJ, and Stage of activity implementation. The results obtained are the installation of a lightweight steel bridge using a composite floor that is able to connect between the villages of Nanggela and Nanggerang in Kali Caringin, RT 04 RW 03, Nanggerang Village, Kec. Tajur Halang, Bogor Regency, West Java and suitable for use by residents around the lightweight steel bridge with composite floors is a technological innovation in the field of bridge structures that can be applied to community service programs based on this study program.